Bone Marrow Aspirate in Cystic Maxillofacial Bony Defects. Issue 3 (May 2019) - U, Vignesh; Mehrotra, Divya; Howlader, Debraj; Kumar, Sumit; Anand, Vaibhav
Abstract : Abstract: Autogenous or alloplastic bone grafts are routinely applied for reconstruction of cystic bone defects. Addition of mesenchymal bone marrow stem cell in osteoconductive alloplastic bone makes it osteoinductive and osteogenic. The purpose of this study was to evaluate the role of bone marrow aspirate in regenerating new bone with hydroxyapatite collagen scaffold in patients with large cystic maxillofacial defects. This prospective randomized study had random allocation of 15 patients with large cystic maxillofacial bony defects in each of the 2 groups. Group I patients received hydroxyapatite granules and bone marrow aspirate in collagen sponge and group II received hydroxyapatite granules only. Clinical and radiologic assessment showed the time taken in bone healing. In group I, the bone defect volume reduction was statistically significant at 3 and 6 months, the postoperative pain and swelling was less, and there was no tooth mobility at 3 months. The authors concluded that use of hydroxyapatite granules with bone marrow aspirate in collagen sponge in maxillofacial bone defects provided early bone regeneration, and faster wound healing. However, to arrive at a definitive conclusion a long-term study with a larger sample size is required.